Virucidal Efficacy of Different Oral Rinses Against Severe Acute Respiratory Syndrome Coronavirus 2. (29th July 2020) - Meister, Toni Luise; Brüggemann, Yannick; Todt, Daniel; Conzelmann, Carina; Müller, Janis A; Groß, Rüdiger; Münch, Jan; Krawczyk, Adalbert; Steinmann, Jörg; Steinmann, Jochen; Pfaender, Stephanie; Steinmann, Eike
Abstract: The ongoing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic creates a significant threat to global health. Recent studies suggested the significance of throat and salivary glands as major sites of virus replication and transmission during early coronavirus disease 2019, thus advocating application of oral antiseptics. However, the antiviral efficacy of oral rinsing solutions against SARS-CoV-2 has not been examined. Here, we evaluated the virucidal activity of different available oral rinses against SARS-CoV-2 under conditions mimicking nasopharyngeal secretions. Several formulations with significant SARS-CoV-2 inactivating properties in vitro support the idea that oral rinsing might reduce the viral load of saliva and could thus lower the transmission of SARS-CoV-2. Abstract : Several oral rinses show significant severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) inactivating properties in vitro, supporting the idea that oral rinsing might reduce the viral load of saliva and could thus lower the transmission of SARS-CoV-2.